2016
DOI: 10.1371/journal.pone.0164224
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Transient Elastography and Comparison with Spleen Length Measurement for Staging of Fibrosis and Clinical Prognosis in Primary Sclerosing Cholangitis

Abstract: BackgroundPatients with primary sclerosing cholangitis (PSC) develop progressive liver fibrosis and end-stage liver disease. Non-invasive and widely available parameters are urgently needed to assess disease stage and the risk of clinical progression. Transient elastography (TE) has been reported to predict fibrosis stage and disease progression. However, these results have not been confirmed in an independent cohort and comparison of TE measurement to other non-invasive means is missing.MethodsIn a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 28 publications
1
33
1
3
Order By: Relevance
“…TE is an ultrasound shear‐wave–based technology that can also measure liver stiffness. Both have been shown to correlate well with the histological stage of fibrosis and outcomes among patients with PSC . Use of MRE may offer several key advantages when compared to TE.…”
Section: Mri/mrcp Overviewmentioning
confidence: 96%
“…TE is an ultrasound shear‐wave–based technology that can also measure liver stiffness. Both have been shown to correlate well with the histological stage of fibrosis and outcomes among patients with PSC . Use of MRE may offer several key advantages when compared to TE.…”
Section: Mri/mrcp Overviewmentioning
confidence: 96%
“…These results need prospective validation, which is currently being performed by the international 5‐year prospective FICUS cohort study within the IPSCSG. A recent study from Germany reported findings similar to those of Corpechot et al and demonstrated good performance for diagnosis and exclusion of higher fibrosis stages (≥F3) with an AUROC of 0.95 …”
Section: Potential Biomarkersmentioning
confidence: 99%
“…For a cutoff of 120 mm, spleen size measured by ultrasound or on MRI was correlated with patient outcome; PSC patients with a spleen size over 120 mm had a median TFS of only 5.2 years . These researchers recently expanded their series to a combined German/French cohort of 210 PSC patients and found the same adequate Harell's c‐statistics for both TE as for spleen length with regard to its predictive power (liver‐related death, LT, and hepatic decompensation) . However, these data are preliminary and, at this time, are not adequate to support spleen size as a surrogate for clinical trials.…”
Section: Potential Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate this, the Enhanced Liver Fibrosis (ELF) Panel was developed and has been shown to predict transplant‐free survival (TFS) . Elastography techniques appear to hold promise to predict clinically relevant events, and prospective validation studies are ongoing . All of these prognostic variables have their own limitations and were examined using traditional statistical methods.…”
mentioning
confidence: 99%